Blood glucose levels in healthy, term, appropriate for gestational age, exclusively breastfed infants - Lineus Hewis; Rulina Suradi; Taralan Tambunan (Indonesian Pediatric Society Publishing House, 2016)
Objective This study aimed to determine blood glucose levels of healthy, term, appropriate for gestational age (AGA), exclusively breastfed infants at the age of 6, 12, 24, 48, and 72 hours of life, and to investigate the incidence of hypoglycemia in those infants. Methods All healthy, term, AGA infants born in Cipto Mangunkusumo General Hospital, Jakarta, who were exclusively breastfed during the recruitment period of December 2003 until February 2004, were included in this study. These infants were subjected to blood glucose level determination at the age of 6, 12, 24, 48, or 72 hours of life, and the clinical signs of hypoglycemia were monitored. Results Two hundred and fifteen blood samples taken from 137 newborns were studied. There was no incidence of hypoglycemia observed, whether symptomatic or asymptomatic. The range of blood glucose levels was between 41 mg/dl and 115 mg/dl. The means and the standard deviations (SD) of the blood glucose lev- els of the 6-, 12-, 24-, 48- and 72-hour old infants were 59.7 (11.98) mg/dl, 64.1 (13.51) mg/dl, 65.9 (14.42) mg/dl, 67.0 (14.95) mg/dl, and 78.6 (16.51) mg/dl, respectively. Conclusions The current concern for hypoglycemia in the popu- lation of healthy, term, AGA, exclusively breastfed infants during the first few days of life was not proven to exist. Therefore, there is no reason to resort to prelacteal feeding in such infants